Degree Sequences and Dominating Cycles in 2-Connected Graphs - Mossine S. Koulakzian (Изд-во НАН РА)
Let G be a graph on n vertices and minimum degree δ with degree sequence δ = d1 ≤ d2 ≤ ... ≤ dn. The minimum degree sum of two nonadjacent vertices in G is denoted by σ2.
Keywords: Mathematics; Graph theory